Pengenalan Potensi Kawasan Sebagai Pondasi Pembangunan Pusat Pendidikan Berbasis Komunitas Lokal Pedesaan - Perdana, Adhi Surya; Rahardjo, Budi; Ikhsani, Ikha Amalia; Ilmi, Miftahul (Jurnal Ilmiah Membangun Desa dan Pertanian, 2021)
Social, economic, institutional, and cultural conditions become the basis of education and provide benefits for science to formulate the introduction of regional potential, regional designations, program development carried out by villages, and routine activities (learning, research, and community service) by students and lecturers of the Faculty of Agriculture Tidar University which has an interest in developing Sidorejo Village, Bandongan District. The research objective is to create an embryonic center for local community-based education in strengthening rural areas that are progressing efficiently, effectively, and sustainably as a form of university connectivity with the local community. This research focuses on identifying the area's potential in a careful village, with a qualitative research method using an ex post facto comparative clause through a social, ethnographic approach. The research was conducted using a purposive sampling technique consisting of village officials, community leaders, youth organizations, family empowerment and welfare, arts and culture actors, business actors, and planning faculty development planners as many as 20 respondents. The results of the study are in the form of identification findings that can be used as objects of community social mapping projections, needs, essential potential, human resource capabilities, institutions, local culture, infrastructure, economy, natural resources, and agriculture to design rural areas to become centers of local community-based education in strengthening, developing and tri dharma of higher education in the fields of agriculture, plantation, animal husbandry, fisheries, and social entrepreneurship.